Character Building Creative, Productive And Competitive Students At Fashion School- Iswi, In Jakarta, Indonesia - Syamsiah, Siti (IJTB (International Journal of Technology And Business), 2017)
This study aims to determine the importance of the formation of the character of each individual that needs to be formed to have the nature and mindset is good, true, and high quality. Formation of character creative, productive and competitive, a force for building the spirit and thoughts of someone in order to be become a human being intelligent, skilled, inventive.Research methods used were interviews, observation, participation, and documentation. Subjects were students of the third semester to the top of the fashion school Academy of Art and Design ISWI, Jakarta, Indonesia.Based on the description in this study, it was explained that the creation of the character of the creative, productive and competitive as applied to students of fashion schools where the author teaches, it is very beneficial for students and the campus. The positive energy generated from the character can be equipped students to independently create entrepreneurs.The implication of this study is an effort to improve students ability to spirit and